2020
DOI: 10.3390/jcm9072181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PrObiotics on the Symptoms and Surgical ouTComes after Anterior REsection of Colon Cancer (POSTCARE): A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: We investigated microbiota changes following surgical colon cancer resection and evaluate effects of probiotics on microbiota and surgical recovery. This randomized double-blind trial was performed at four medical centers in South Korea. Of 68 patients expected to undergo anterior sigmoid colon cancer resection, 60 were eligible, of whom 29 and 31 received probiotics and placebo, respectively, for four weeks, starting at one week preoperatively. Third- and/or fourth-week information on anterior resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 31 publications
0
63
0
1
Order By: Relevance
“…Searches for the overarching umbrella project of 10 natural health products retrieved 4653 records in total, which were screened in duplicate. A total of 45 probiotics articles were included, reporting on 42 unique studies, comprising 39 reports (listed alphabetically under the References) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], of 36 randomized controlled trials involving 3305 participants and 6 nonrandomized and cohort studies [ 72 , 73 , 74 , 75 , 76 , 77 ]. A study flow diagram is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches for the overarching umbrella project of 10 natural health products retrieved 4653 records in total, which were screened in duplicate. A total of 45 probiotics articles were included, reporting on 42 unique studies, comprising 39 reports (listed alphabetically under the References) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], of 36 randomized controlled trials involving 3305 participants and 6 nonrandomized and cohort studies [ 72 , 73 , 74 , 75 , 76 , 77 ]. A study flow diagram is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This trial in sigmoid colon cancer utilized Bifidobacterium animalis subsp. lactis HY8002 + Lactobacillus casei HY2782 + L. plantarum HY7712 + xylooligosaccharides + fructooligosaccharides [ 54 ]. Other postoperative complications not captured above are also presented for additional safety data ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…L. casei HY2782 is used as a starter strain for Korean Yakult fermented milk products. Previous studies have shown that L. casei HY2782 has various functions such as increasing the expression of interleukin 12 in dendritic cells [18] and preventing the toxic effect induced by particulate matter [19,20]. Previous studies found that growth and metabolism mostly cease after 24 h of incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Ten of the studies [ 16 , 22 , 23 , 27 29 , 31 , 32 , 34 , 36 ] conducted an appropriate randomization process. Deviations from intended interventions were evaluated as a low bias risk in six studies [ 16 , 20 , 22 , 31 , 34 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the studies [ 16 , 22 , 23 , 27 29 , 31 , 32 , 34 , 36 ] conducted an appropriate randomization process. Deviations from intended interventions were evaluated as a low bias risk in six studies [ 16 , 20 , 22 , 31 , 34 , 36 ]. Missing outcome data, measurement of the outcome, and selection of the reported result in all studies were assessed as a low bias risk ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%